Factors that shape learner achievement in socially disadvantaged and rural contexts: a social realist study in two rural senior secondary schools in Omusati region, Namibia - Shilongo, Erica (Rhodes University, Faculty of Education, Department of Education, 2018)
Learners' performance and the reasons for either achievement or failure in school has lo ng been a topic of debate. In early research on academic achievement, theorists, educators, biologists and psychologists traditionally focused on the learners from socially disadvantaged family backgrounds who underachieve. Much of the debate internationally centred on whether learner academic achievement / underachievement is a product of hereditary traits or the social context. In particular, arguments for and against whether the reasons for the achievement / underachievement of children from socially disadvantaged families are genetic or the social context in which they find themselves continue unabated. Such explanations do not provide insight into why it is that despite familial (genetic) and social circumstances (social disadvantage), some children succeed and/or are able to act outside expectations of failure. Little research has focused on those in the same or similar contexts who are achieving academic success despite their limiting circumstances and the reasons for their success. This study used a social realist lens to investigate the factors that shape the academic achievement of 12 learners in two rural senior secondary schools in Omusati region, Namibia. All 12 learners are from low socioeconomic family backgrounds. The data was collected through survey, interviews with learners, parents and teachers, field notes and document analysis. The main finding of the study show that contrary to research that portrayed learners' achievement as determined either by heredity or social contexts, the 12 learners constantly used their agentic possibilities to navigate constraining structural and cultural conditions at regional, familial and school levels to achieve academic success. Their agency was shaped by the socioeconomic conditions in their lives, namely, socioeconomic deprivation; large extended families in rural households, lack of amenities and utilities in their families, participation in household chores, experience of family tragedies and of changes when they were young.
Keywords: Academic achievement-- Namibia Omusati; High school students-- Namibia Omusati Social conditions; Rural schools-- Namibia Omusati; Education, Rural-- Namibia Omusati; Social realism